The Legal Implications on Cancellation of Notaries which can be Canceled by Law - Akhmad Mufasirin; Aryani Witasari (Sultan Agung Notary Law Review, 2022)
The purpose of this study is to analyze and explain the implementation of the cancellation of a notarial deed which can be canceled by law. To analyze and explain the legal implications of the cancellation of a notarial deed .The method used by the researcher is Sociological Jurisdiction and The specifications in this study are descriptive. Based on the results of the study that Implementation of Cancellation of Notary Deeds which can be canceled according to law is the cancellation of notarial deeds can occur due to several things that objective conditions are not fulfilled; absolute incompetence; inability to act; relative incompetence; contrary to the law; public order or decency; fulfillment of legal events in the agreement on the condition that it is void; a defect of will; abuse of circumstances; default as a condition of cancellation; non-fulfillment of formal agreements. Legal Implications for Cancellation of Notary Deed, namely canceled notary deed, cancelable notary deed, and null and void notary deed. 1) A notarial deed that can be canceled is a deed that is canceled by the appearers themselves with a notarial deed based on reasons known to the presenters themselves.